Analisis Ketidakseimbangan Beban pada Transformator Bambang Djaja ULP Fakfak - Rusliadi Rusliadi; Yulianto La Elo; Naomi Lembang (Pusat riset dan Inovasi Nasional, 2022)
Research has been carried out on the load imbalance analysis on the transformer with the aim of knowing the percentage of load imbalance on the transformer. From the results of the analysis that has been carried out, it is known that the percentage of transformer loading is unbalanced and is in bad condition because it exceeds the balance standard that has been set, which is above 25% with a percentage for line 1 of 60% during the day and 80% at night. While on line 2 has a percentage of 35% during the day and 33% during the day.